Das Theater von Ephesos. Archäologischer Befund, Funde und Chronologie, Textband - Ruggendorfer, Peter (Verlag der Österreichischen Akademie der Wissenschaften, 2017)
In this volume of the "Forschungen in Ephesos" the recent archaeological examinations at the Theater of Ephesus are published. Beside the results of the excavations the volume incorporates the analysis of the various find categories, such as pottery and glass, terracotta, sculptures, small finds, coins as well as archaeozoological and epigraphical finds. With this, the reader can comprehensively impart and review the architectural development of the theater in the course of the eight building or usage phases.